Privacy Control In Social Networks By Trust Aware Link Prediction - Syam Prasad Dhannuri; Sanjay Kumar Sonbhadra; Sonali Agarwal; P. Nagabhushan; M. Syafrullah; Krisna Adiyarta (Proceeding of the Electrical Engineering Computer Science and Informatics, 2019)
Social networks are exceedingly common in today’s society. A social network site is an online platform where people build social relations with others and share information. For the last two decades, rapid growth in the number of users and applications with these social networking sites, make the security as the most challenging issue. In this virtual environment, some greedy people intentionally perform illegal activities by accessing others’ private information. This paper proposes a novel approach to detect the illegal access of a particular’s information by using trustaware link prediction. The facebook dataset is used for experiments and the results justify the robustness andtrustworthiness of the proposed model.